2015
DOI: 10.1155/2015/984767
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Symptoms and Its Correlates: A Study on Tribe and Caste Population of East India

Abstract: Present study aimed to compare the incidence of menopausal problems and concomitants between tribe and caste population. This cross section study was conducted in five villages of West Bengal, a state in the eastern part of India. This study was conducted between two different ethnic groups—one of the “Particularly Vulnerable Tribal Groups (PTG)” of India named as “Lodha” and the other was a Bengali speaking caste population. A total number of 313 participants were finally recruited for this study. Study parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In the present study, GSM was more in patients with low socioeconomic status (OR= 1.40, P= 0.295551) and significantly associated with lower educational level (OR= 2.07, P= 0.026647) (table 4). In their study, on postmenopausal women, aged 45-55years, Doyel Dasgupta et al 23 found a relationship among low educational level and rural residential status.…”
Section: Resultsmentioning
confidence: 89%
“…In the present study, GSM was more in patients with low socioeconomic status (OR= 1.40, P= 0.295551) and significantly associated with lower educational level (OR= 2.07, P= 0.026647) (table 4). In their study, on postmenopausal women, aged 45-55years, Doyel Dasgupta et al 23 found a relationship among low educational level and rural residential status.…”
Section: Resultsmentioning
confidence: 89%
“…This is at variance with a study that reported association between early menarche and vasomotor symptoms. 38 Previous studies however reported association between late menarche and psychosocial symptoms. 39 Menopausal women within the age range of 45–54 years were found to be linked with psychosocial and vasomotor symptoms in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Problems were differed according to their socio-demographic variable like tribe and caste. Dasgupta et al (2015) Alizadeh M et al conducted a study which showed that menopausal symptoms occurred higher in older age. Additionally, frequencies of menopausal symptoms were less in employed women than retired or homemakers.…”
Section: Review Of Literaturementioning
confidence: 99%